The economic viability of the use of urea with urease inhibitor in cotton grown in the Cerrado of Central Brazil - Leite, Rafael da Costa; Leal, Aguinaldo José Freitas; Piati, Gabriel Luiz; Vendruscolo, Eduardo Pradi; Barreto, Rafael Ferreira [UNESP]; Lima, Sebastião Ferreira de; Zoz, Tiago; Kaneko, Flávio Hiroshi; Zanella, Mayara Santana (Elsevier, 2023)
The cotton crop has a high demand for nitrogen fertilizers. However, an adequate supply of this nutrient may be difficult in regions with a tropical climate, requiring the introduction of technologies that provide better nitrogen availability to plants, such as urease inhibitors. The study aimed to evaluate the economic viability of using urease inhibitor in the treatment of urea granules for fertilizing cotton grown in the summer in a tropical region. The experimental design was randomized blocks with four replications in a 3 × 5 factorial scheme. The treatments consisted of urea treated with 0.045% and 0.060% urease inhibitor (N-(n-butyl)thiophosphoric triamide - NBPT) and urea without urease inhibitor applied as topdressing, in doses of 0, 40, 80, 120 and 160 kg ha−1, divided into two applications, at 30 and 50 days after emergence. Fiber yield, effective operational cost, total operational cost, total cost, gross revenue, gross margin, net operational margin, net margin, profitability index, equilibrium price, and equilibrium yield were determined. In an agricultural year with rainfall close to the application of N in topdressing, the use of N at a dose of 120 kg ha−1 in the form of urea, associated with the urease inhibitor, promoted greater profitability of the cotton crop, as well as the use of urea regardless of the use of urease inhibitor. The urease inhibitor did not interfere with cotton fiber yield.
Keywords: Gossypium hirsutum; NBPT; Production cost; Profitability